Cell‐Laden Multiple‐Step and Reversible 4D Hydrogel Actuators to Mimic Dynamic Tissue Morphogenesis. Issue 9 (1st March 2021) - Ding, Aixiang; Jeon, Oju; Tang, Rui; Lee, Yu Bin; Lee, Sang Jin; Alsberg, Eben
Abstract: Shape‐morphing hydrogels bear promising prospects as soft actuators and for robotics. However, they are mostly restricted to applications in the abiotic domain due to the harsh physicochemical conditions typically necessary to induce shape morphing. Here, multilayer hydrogel actuator systems are developed using biocompatible and photocrosslinkable oxidized, methacrylated alginate and methacrylated gelatin that permit encapsulation and maintenance of living cells within the hydrogel actuators and implement programmed and controlled actuations with multiple shape changes. The hydrogel actuators encapsulating cells enable defined self‐folding and/or user‐regulated, on‐demand‐folding into specific 3D architectures under physiological conditions, with the capability to partially bioemulate complex developmental processes such as branching morphogenesis. The hydrogel actuator systems can be utilized as novel platforms for investigating the effect of programmed multiple‐step and reversible shape morphing on cellular behaviors in 3D extracellular matrix and the role of recapitulating developmental and healing morphogenic processes on promoting new complex tissue formation. Abstract : Multilayered cell‐laden hydrogel actuators (CHAs) are developed to mimic dynamic tissue morphogenesis. The CHAs, which show multiple deformations programmably and controllably, enable defined self‐folding and/or user‐regulated, on‐demand‐folding into specific 3D architectures under physiological conditions. With these multilayered cytocompatible systems, potential applications in the biomedical field, such as morphodynamic tissue engineering, are demonstrated.